Risco, saúde e obesidade na prática de trabalho dos policiais militares do Estado de São Paulo - Magalhães, Bóris Ribeiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This investigation comes from an institutional survey made in 2007, performed between Military Police from the State of São Paulo which points overweight and obesity with high body mass index (BMI) in the effective. The intent is to investigate the impacts of the daily work experience, triggered in the subjectivity of expectations, risks and interactions in the professional practice about health and conduction of the military police body. Submitted to the rules that ensure the productivity for the use of strength and to the control of social order, the policemen have their BMI increased in professional practice, get sick and contradict the normativities present in the institutional management and social speeches. Different methodological approaches of qualitative bias operationalized by the biopolitcs concept of Michel Foucault will allow us to understand the disease factors and the dynamic of the increase of weight among policemen, the power relations focused on the control of these abnormalities, and its dangers to the institution, in search for a healthy life. The observation proposed has as an empirical basis the Military Police Battalion from the country – state São Paulo, that measured incidences of obesity among their policemen, and develops an action of facing the disease since 2011 with a program of “Weight Reduction & Improvement of Quality of Life” for the Military Police.

A presente investigação parte de levantamento institucional de 2007, realizado entre Policiais Militares do Estado do São Paulo, que aponta sobrepeso e obesidade com elevados Índices de Massa Corporal (IMC) no efetivo. O intento é investigar os impactos das experiências laborais cotidianas, acionadas na subjetivação das expectativas, dos riscos e interações na prática profissional, sobre a saúde e condução do corpo do policial militar. Submetidos às normas que asseguram a produtividade para o uso da força e para o controle da ordem social, os policiais na prática profissional têm seu IMC aumentado, adoecem e contrariam as normatividades presentes no gerenciamento institucional e nos discursos sociais. Diferentes abordagens metodológicas de viés qualitativo operacionalizadas pelo conceito de biopolítica de Michel Foucault permitiram entender os fatores de adoecimento e a dinâmica do aumento de peso entre policiais, as relações de poder voltadas para o controle dessas anormalidades, e seus perigos para a instituição, em busca de uma vida saudável. A observação proposta tem como base empírica um Batalhão de Polícia Militar do Interior do estado de São Paulo, que mensurou incidências de obesidade entre seus policiais, e desenvolveu uma ação de enfrentamento da doença a partir do ano de 2011, com o “Programa de Redução de Peso e Melhoria de Qualidade de Vida da PM”.
Keywords: São Paulo (Estado) Policia Militar; Obesidade; Fatores de risco; Biopolitica; Corpo humano; Poder (Ciencias sociais); Risk factors